TMIC-34. INVESTIGATING THE EFFECT OF IRON IN GLIOBLASTOMA CELL POLARIZATION AND MIGRATION. (14th November 2022) - Shenoy, Ganesh; Palsa, Kondaiah; Wade, Quinn; Khunsriraksakul, Chachrit; Khristov, Vladimir; Slagle-Webb, Becky; Lathia, Justin; Wang, Hong-Gang; Connor, James
Abstract: Glioblastoma represents one of the most difficult-to-treat malignancies as evidenced by the poor prognosis associated with a diagnosis. The ability of glioblastoma cells to diffusely infiltrate into healthy brain tissue renders complete surgical resection challenging. Consequently, a large majority of glioblastoma patients end up with recurrent disease despite receiving maximally feasible surgical resection and rigorous chemoradiation. This work examined how modulation of cellular iron levels in T98G and LN229 glioblastoma cells impacted migratory capacity. Treatment of T98G or LN229 glioblastoma cells with iron in the form of ferric ammonium citrate (FAC) resulted in significantly reduced migration as assessed by time-lapse phase contrast imaging and wound healing assays. The iron-induced reduction in migration was able to be rescued by the addition of equimolar concentrations of deferoxamine, an iron chelator. Cellular proliferation in response to the iron treatments was quantified using both optical confluence and nucleic-acid-based proliferation assays and it was found that iron treatment at the concentrations used for the migration assays (0 – 300 µM FAC) did not result in reduced proliferation. Mechanistically probing iron's impact on cell migration revealed that addition of iron resulted in decreased expression of Cdc42, a Rho GTPase that is essential to determining cellular polarity during migration. Functional cellular polarization assays further confirmed that reduced expression of Cdc42 corresponded to reduced cellular polarization. Bioinformatic analysis of CDC42 transcripts revealed the presence of potential iron-responsive-elements that may drive the iron-induced reduction in Cdc42 expression. This work highlights the importance of iron biology in impacting glioblastoma cell phenotype and potentially glioblastoma patient outcomes.